Achieving glycaemic control without weight gain, hypoglycaemia, or gastrointestinal adverse events in type 2 diabetes in the SUSTAIN clinical trial programme. Issue 10 (9th July 2018) - DeVries, J. Hans; Desouza, Cyrus; Bellary, Srikanth; Unger, Jeffrey; Hansen, Oluf K. H.; Zacho, Jeppe; Woo, Vincent
Abstract : Aim: To evaluate the potential for semaglutide to help people with type 2 diabetes (T2D) achieve glycated haemoglobin (HbA1c) targets while avoiding unwanted outcomes, such as weight gain, hypoglycaemia and gastrointestinal (GI) side effects. Materials and methods: Data from the phase IIIa SUSTAIN 1 to 5 clinical trials were analysed. Participants had inadequately controlled T2D and were drug‐naïve (SUSTAIN 1) or on a range of background treatments (SUSTAIN 2 to 5). The main protocol‐specified composite endpoint was the proportion of participants achieving HbA1c <53 mmol/mol (7.0%) at end of treatment (30 or 56 weeks) without weight gain and with no severe or blood glucose (BG)‐confirmed symptomatic hypoglycaemia. A post hoc composite endpoint was the proportion of participants achieving the primary composite endpoint without moderate or severe GI adverse events (AEs). Results: Across the SUSTAIN trials 1 to 5, 3918 participants with T2D were randomized to once‐weekly subcutaneous semaglutide 0.5 mg, 1.0 mg, or comparators (placebo, sitagliptin 100 mg, exenatide extended release 2.0 mg or insulin glargine). The proportion of participants achieving HbA1c <53 mmol/mol (7.0%) with no weight gain and no severe/BG‐confirmed symptomatic hypoglycaemia was 47% to 66% (semaglutide 0.5 mg) and 57% to 74% (semaglutide 1.0 mg) vs 7% to 19% (placebo) and 16% to 29% (active comparators; all P < .0001). More participants achieved the primary composite endpoint with no moderate or severe GI AEs with semaglutide vs comparators (all P < .0001). Conclusion: Semaglutide helped more people with T2D achieve HbA1c targets than did comparators in the SUSTAIN 1 to 5 trials, while avoiding unwanted outcomes such as weight gain, hypoglycaemia and GI side effects.